Bearing allostatic load: insights into a more equitable future within cardio-oncology. Issue 12 (December 2022) - Barrett, Matthew; Wilcox, Nicholas S.; Huang, Anran; Levy, Richard; Demissei, Biniyam; Narayan, Vivek; Ky, Bonnie
Abstract : Chronic stress is often regarded as a significant cause of morbidity and mortality; however, the mechanistic link between stress and various disease states has not yet been fully characterized. We explore the concept of allostatic load, a measurement of the physiological burden of chronic stress, as well as its potential role in disease pathogenesis as it relates to cardiovascular disease, cancer, and health-related disparities. Building from this framework, we then posit the potential implications of allostatic load on patient care and research in cardio-oncology. We identify allostatic load as a potential clinically actionable tool to improve health equity in cardio-oncology. Highlights: The physiological burden of chronic stress is governed by both physical stressors and social determinants of health. Allostatic load serves as a measure of chronic stress through the utilization of an array of stress-related biomarkers. Higher allostatic load has been associated with adverse cardiovascular and cancer outcomes. Black and Hispanic individuals tend to have a higher allostatic load than non-Hispanic White individuals. Several studies have suggested that Black patients are also more susceptible to the cardiotoxic effects of several cancer therapies; allostatic load may explain this susceptibility.